The Great Recession vs. the Great Depression. Stylised Facts on Siblings that Were Given Different Foster Parents - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2009)
This paper compares the depth of the recent crisis and the Great Depression. We use a new data set, namely seven activity indicators, to compare the drop in activity in industrialised countries. This is done under the assumption that the recent crisis levelled off in mid-2009 for production and will do so for unemployment in 2010. Our data indicate that the recent crisis did indeed have the potential to turn into another Great Depression, as shown by the speed and simultaneity of the decline during the first nine months. However, if we assume that a large second dip can be avoided, the drop in all indicators overall will have been smaller than during the Great Depression. This holds true specifically for GDP, employment and prices, but is less true for manufacturing output. The difference in the depth of the crises reflects the differences in policy reaction. This time monetary policy and fiscal policy were applied courageously, speedily and were partly internationally coordinated. For several years during the Great Depression fiscal policy tried to stabilise budgets instead of aggregate demand, and either monetary policy was not applied or it was rather ineffective insofar as deflation turned lower nominal interest rates into higher real rates. Only future research will be able to prove the exact impact of economic policy, but the current tentative conclusion is that economic policy prevented the recent crisis from developing into a second Great Depression. This is also a partial vindication for economists. The majority of them might not have been able to predict the crisis, but it shows that the science did learn its lessons from the Great Depression and was able to give decent policy advice to at least limit the depth of the recent crisis.
Keywords: 330; Finanzkrise; Wirtschaftskrise; Wirtschaftsgeschichte; Vergleich; Stabilisierungspolitik; Antizyklische Finanzpolitik; Welt